PERAN PEMERINTAH DESA TERHADAP PEMBERANTASAN TINDAK PIDANA PERJUDIAN KARTU REMI YANG DILAKUKAN DI ACARA DUKA DI DESA SILINA KECAMATAN SIMUK KABUPATEN NIAS SELATAN - Fasralin Ojan Bago (LPPM Universitas Nias Raya, 2024)
Regarding the eradication of criminal acts of playing card gambling carried out at mourning events in Silina Village, Simuk District, South Nias Regency, the village government has not provided a formal response to the card gambling carried out so far. sorrow. One example of a criminal act of gambling is explained in Article 2 paragraph (1) of Law Number 7 of 1974 concerning Control of Gambling which regulates the length of the learning period at a maximum of thirty years or at least two hundred and fifty thousand rupiah. Playing card gambling is betting a certain amount of money using playing cards where the winner gets the betting money or in other words, fighting of fate is a form of game which is a game of chance for those who gamble. The type of research used is sociological legal research with a direct approach to the field, namely to examine applicable legal provisions and what happens in the real life of society. Deductive techniques are used to draw conclusions after descriptive data analysis of primary and secondary data obtained from library materials. Research findings and discussions resulted in the conclusion that although the village government had attempted to prohibit the sale of playing cards through village council meetings, the community had not followed the prohibition because there were no police officers (Bhabinkamtibmas) on duty and there was no written letter. law regarding the prohibition of card games as specified in Law Number 7 of 1974 concerning Gambling Control, Article 2 paragraph (1). According to the author, the village government must involve the community